2014
DOI: 10.5433/1679-0359.2014v35n5p2399
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative burst and the activity of defense-related enzymes in compatible and incompatible tomato-Alternaria solani interactions

Abstract: The production of reactive oxygen species (ROS), hypersensitive response (HR), and the activity of the enzymes guaiacol peroxidase, catalase, polyphenol oxidase, β-1,3-glucanase and chitinase, were studied in leaves of resistant [CNPH 1287 (Solanum habrochaites syn. Lycopersicon hirsutum)] and susceptible [Santa Cruz Kada (S. lycopersicum syn. L. esculentum)] tomato genotypes inoculated with Alternaria solani. Leaves were collected at the time of inoculation and at 4, 8, 12, 24, 48, 72, 96 and 120 hours post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Sacc. The decreased activity of CAT in infected leaves of all cultivars over healthy leaves suggests that CATwas not operating as H 2 O 2 -scavenging enzyme but favors the H 2 O 2 accumulation as indicated by Balbi-Peña et al (2014) which may be involved in defence against foliar fungal disease complex.…”
Section: Resultsmentioning
confidence: 96%
“…Sacc. The decreased activity of CAT in infected leaves of all cultivars over healthy leaves suggests that CATwas not operating as H 2 O 2 -scavenging enzyme but favors the H 2 O 2 accumulation as indicated by Balbi-Peña et al (2014) which may be involved in defence against foliar fungal disease complex.…”
Section: Resultsmentioning
confidence: 96%
“…Other studies have confirmed that temperatures in the range 25-32°C, favor the development of black spots on tomato and epidemic disease (BALBI-PEÑA et al, 2006;SALUSTIANO et al, 2006). The relative humidity ranged from 60 to 90% during the test which may have promoted the presence of free water on the leaf surface, a fundamental factor for germination, infection and sporulation.…”
Section: Resultsmentioning
confidence: 77%
“…The relative humidity ranged from 60 to 90% during the test which may have promoted the presence of free water on the leaf surface, a fundamental factor for germination, infection and sporulation. Researchers demonstrated that A. solani occurs in the infection process in a 14-26°C temperature range, with a relative humidity around 100% during the first 24 h, establishing conditions for the development of the epidemic (ROTEM, 1994;PAUL et al, 2004;BALBI-PEÑA et al, 2006;SALUSTIANO et al, 2006). Such conditions are evident from the 51 DAT indicating a significant increase in disease severity genotypes (Figure 2).…”
Section: Resultsmentioning
confidence: 86%
“…To better understand the mechanism of resistance, the expression β-1,3 -glucanase gene was investigated in all EC-treated tomato plants in our study. This gene encodes one of the pathogenesis-related proteins (PR protein) that are included in several plant-pathogen interactions and associated with defense against plant diseases ( Sharifi et al, 2012 ; Balbi-Peña et al, 2014 ). Plant β - 1 ,3-glucanases play an important role in controlling the outcome of both symbiotic and antagonistic plant-microbe interactions by destroying non-self-glucan structures.…”
Section: Discussionmentioning
confidence: 99%